Acceptance and uptake of influenza vaccines in Asia: A systematic review. Issue 35 (14th August 2019) - Sheldenkar, Anita; Lim, Fann; Yung, Chee Fu; Lwin, May O.
Abstract: In Asia, the public health burden of influenza is significant despite the existence of efficacious influenza vaccines. Annual seasonal influenza vaccination can reduce the incidence of influenza significantly, yet influenza vaccination coverage remains low in this part of the world. As a densely populated region with varying climatic zones and a larger proportion of developing countries compared to the West, Asia is at increased risk of influenza. To provide a more comprehensive and nuanced understanding of the Asian region, the key objective of this systematic review is to examine the determinants of vaccination uptake in Asia, beyond that of existing studies that have largely been western-centric. We carried out a systematic review of peer-reviewed scientific research, examining the key determinants, acceptance and uptake of influenza vaccinations across Asia. A comprehensive search strategy was defined to capture studies that met the inclusion criteria of articles published in English, from 2008 to 2018, focusing on adult populations within Asia. A total of 83 relevant studies were appraised in this review. Analyses of the extant data confirmed that vaccination rates within Asia are low, and that most countries lack scientific research on vaccination behaviours. Studies were categorised into four different population groups: healthcare workers, high risk groups, general population and uniform groups. The motivators and deterrents for vaccine uptake varied according to population groups and characteristics. Both general populations and healthcare workers were concerned with vaccine safety and efficacy, and recommendations from health authorities were influential in vaccine uptake within the other populations. The findings suggest that further research is needed within a broader range of Asian countries to garner greater in-depth knowledge of vaccination behaviours in the region. In particular, influenza vaccination programs within Asia should focus on improving engagement more effectively, through greater relatability and transparency of data when educating the public.